The determinants of public deficit volatility - Luca Agnello; Ricardo M. Sousa (European Central Bank (ECB), 2009)
This paper empirically analyzes the political, institutional and economic sources of public deficit volatility. Using the system-GMM estimator for linear dynamic panel data models and a sample of 125 countries analyzed from 1980 to 2006, we show that higher public deficit volatility is typically associated with higher levels of political instability and less democracy. In addition, public deficit volatility tends to be magnified for small countries, in the outcome of hyper-inflation episodes and for countries with a high degree of openness.
Keywords: E31; E63; 330; institutions; political instability; public deficit; Volatility; Haushaltsdefizit; Volatilität; Politische Instabilität; Demokratie; Institutionelle Infrastruktur; Momentenmethode; Welt